2008
DOI: 10.1002/bem.20446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term W‐CDMA mobile phone base station exposure on women with or without mobile phone related symptoms

Abstract: To investigate possible health effects of mobile phone use, we conducted a double-blind, cross-over provocation study to confirm whether subjects with mobile phone related symptoms (MPRS) are more susceptible than control subjects to the effect of electromagnetic fields (EMF) emitted from base stations. We sent questionnaires to 5,000 women and obtained 2,472 valid responses from possible candidates; from these, we recruited 11 subjects with MPRS and 43 controls. There were four EMF exposure conditions, each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
1
34
0
15
Order By: Relevance
“…None of these trials [17][18][19][20] revealed a correct field detection rate better than expected by chance ( Fig. 2) and there was no evidence that individuals who were hypersensitive to electromagnetic fields were more likely to determine correctly the presence or absence of exposure than individuals who were not hypersensitive (P = 0.66).…”
Section: Field Perceptionmentioning
confidence: 84%
See 3 more Smart Citations
“…None of these trials [17][18][19][20] revealed a correct field detection rate better than expected by chance ( Fig. 2) and there was no evidence that individuals who were hypersensitive to electromagnetic fields were more likely to determine correctly the presence or absence of exposure than individuals who were not hypersensitive (P = 0.66).…”
Section: Field Perceptionmentioning
confidence: 84%
“…The details of these studies are summarized in Table 1 (available at: http://www.who.int/bulletin/volumes/88/12/09-071852). Three trials used a UMTS antenna to create controlled exposure circumstances 17,19,20 and one study evaluated all three mobile phone frequency bands. 18 In total, 282 healthy adults, 40 healthy adolescents and 88 individuals with hypersensitivity Research to electromagnetic fields were included in these four studies.…”
Section: Non-specific Symptoms Of Illhealthmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, Furubayashi et al [2009] reported that 1.2% of females showed mobile phone‐related and other unusual symptoms around telecommunication masts; however, further reports concerning EHS among the Japanese population are lacking. As well, the number of people with an EHS condition varies between countries.…”
Section: Introductionmentioning
confidence: 99%